Yolk fatty acid content, lipid health indices, and oxidative stability in eggs of slow-growing Sasso chickens fed on flaxseed supplemented with plant polyphenol extracts - Tadesse, D.; Retta, N.; Girma, Mekonnen; Ndiwa, Nicholas N.; Dessie, Tadelle; Hanotte, Olivier H.; Getachew, P.; Dannenberger, Dirk; Maak, S. (MDPI, 2023)
Previous attempts to increase the level of flaxseed in hens’ diet for the production of n-3 polyunsaturated fatty acids (n-3 PUFAs)-enriched eggs have been commonly associated with undesirable effects on production efficiency, lipid health indices, and oxidative stability of eggs, requiring adequate research attention. This study investigated the effects of feeding a moderate level of flaxseed (FS) and plant polyphenol extracts (PPEs) on fatty acid content, oxidative stability, and lipid health indices in eggs of slow-growing Sasso T451A laying hens. One hundred and five hens were assigned to five groups (seven replicates of three) and fed on FS (75 g flaxseed and no antioxidants), VE8 (75 g flaxseed and 800 mg vitamin E), TS8 (75 g flaxseed and 800 mg Thymus schimperi), DA8 (75 g flaxseed and 800 mg Dodonaea angustifolia), and CD8 (75 g flaxseed and 800 mg Curcuma domestica) extract per kg diets. The egg yolk content of eicosapentaenoic acid (EPA, C20:5 n-3) in the DA8, TS8, and CD8 diets and docosahexaenoic acid (DHA, C22:6 n-3) in TS8 and CD8 diets significantly (p < 0.05) increased compared with the FS diet. The FS diet significantly increased the malondialdehyde (MDA) content in egg yolks, whereas the TS8 diet decreased it by 67% (p < 0.05). Little difference was observed in yolk fatty acid content between cooked and raw eggs. Production of n-3 PUFA-enriched eggs with favorable lipid health indices was possible through inclusion of PPEs extracted from local plant species grown in Ethiopia and a moderate dose of flaxseed in the diet of laying hens.